Effects of sufentanil in combination with dexmedetomidine for patient-controlled intravenous analgesia after renal transplantation - Ma, Jun; Yang, Yawen; Sun, Linhao; Wu, Tingting (Vojnosanitetski pregled, 2025)
Background/Aim. Nowadays, the most convenient analgesic method is patient-controlled intravenous injection of one or more adjuvant drugs. The aim of our study was to evaluate the effects of sufentanil plus dexmedetomidine for patient-controlled intravenous analgesia (PCIA) after renal transplantation. Methods. Seventy-eight patients receiving living-related renal transplantation under general anesthesia were selected. Radioisotope scanning was performed, and the single glomerular filtration rate of the unilateral kidney was ≥ 40 mL/min/1.73 m2. The control group (CG) and observation group (OG) (39 patients in each group) were analgesic with sufentanil and sufentanil plus dexmedetomidine, respectively. When the Visual Analogue Scale (VAS) score exceeded 4 points, 0.05 mg/kg oxycodone was intravenously injected for remedial analgesia. Plasma levels of endothelin, urea nitrogen, and creatinine were measured by radioimmunoassay. Heart rate (HR), mean arterial pressure, oxygen saturation, VAS score, and sedation score were recorded before anesthesia and after surgery. Analgesic remediation rate, number of effectively pressing the PCIA pump, and incidence rate of adverse reactions within 48 hrs after surgery were recorded. Results. HR of OG was significantly lower than that of CG 6 and 12 hrs after surgery (p
Keywords: analgesia; analgesia, patient-controlled; anesthesia, intravenous; kidney transplantation; postoperative period